2010
DOI: 10.1254/jphs.10050fp
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Itch-Associated Response Induced by Repeated Application of Oxazolone in Mice

Abstract: Abstract. We investigated pharmacological characteristics of the itch-associated response to chronic dermatitis induced by 4-ethoxymethylene-2-phenyl-2-oxazolin-5-one (oxazolone) repeated application in mice. Application of an oxazolone challenge to mice with oxazolone-induced chronic dermatitis evoked severe and transient scratching behavior for up to 1h. Thereafter, mild and continuous scratching behavior was observed for at least 8 h. Both severe and continuous scratching behaviors were suppressed by the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
1
19
0
1
Order By: Relevance
“…3,37) LTB 4 was shown to be involved in scratching in mice with chronic allergic dermatitis and allergic conjunctivitis, 3,32,38) but not in those with acute cutaneous allergy. 39) There are two LTB 4 receptor subtypes, BLT 1 and BLT 2 , which have high and low binding affinities for LTB 4 , respectively.…”
Section: Lipid Mediatorsmentioning
confidence: 99%
“…3,37) LTB 4 was shown to be involved in scratching in mice with chronic allergic dermatitis and allergic conjunctivitis, 3,32,38) but not in those with acute cutaneous allergy. 39) There are two LTB 4 receptor subtypes, BLT 1 and BLT 2 , which have high and low binding affinities for LTB 4 , respectively.…”
Section: Lipid Mediatorsmentioning
confidence: 99%
“…In our previous study, we demonstrated that the scratching behavior in this model was suppressed by an opioid receptor antagonist, suggesting that this behavior is an itch-associated response (12). Gabapentin and pregabalin have previ- ously been reported to have an anti-nociceptive action in neuropathic pain models (16 -18).…”
Section: Discussionmentioning
confidence: 61%
“…We recently reported that mice that received repeated applications of oxazolone showed an antigen-induced severe scratching behavior, followed by chronic dermatitis-induced continuous scratching behavior (12). We have also shown that these mice respond similarly to human patients in terms of the therapeutic activity of anti-itch drugs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, the magnitude of the acanthosis induced by repeated applications of OXA in the CB2-KO mice was significantly reduced compared with WT mice. It has been reported that repeated application of OXA is associated with increased immunoglobulin-E (IgE) in serum and Th2 cytokines at the site of dermatitis (Kitagaki et al, 1995;Tsukumo et al, 2010). Taniguchi et al (2007) had reported that the pinna acanthosis was accompanied by an increase in the amount of epithelium, over-expression of the nerve growth factor (NGF) in the epithelium, and cuticle expression of the p75-positive fiber that plays a role in epithelial thickening.…”
Section: Discussionmentioning
confidence: 99%